Use of interactive methods in teaching some subjects of "Discrete Mathematics and Mathematical Logic" - Ismoilova Dildora Erkinovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, "Working with red and green cards" method is applied to the teaching process, their advantages and disadvantages are listed. It shows what kind of questions can be asked when using these methods.